P084 Salivary gland epithelial cells from sjÖgrens' patients increase B lymphocytes survival and activation. (March 2019) - Rivière, E; Pascaud, J; Virone, A; Ly, B; Paoletti, A; Rohmer, J; Bitoun, S; Nocturne, G; Mariette, X
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Primary Sjögren's syndrome (pSS) is a chronic autoimmune disorder characterized by lymphocytic infiltrates and destruction of the salivary glands (SG). Several lines of evidence support the hypothesis that SG epithelial cells (SGECs) are not only the target of autoimmunity in pSS but may also play a role for its initiation and maintenance. Objectives: To study the survival and the activation of B lymphocytes cocultured with SGECs from pSS patients compared to controls. Methods: Primary cultures of SGECS were established from minor SG biopsies. Patients had pSS according to 2016 EULAR/ACR criteria and controls had sicca symptoms without any antibodies and with normal SG biopsies. The coculture involved B lymphocytes isolated by CD19 magnetic bead positive selection from healthy donors' blood (purity >80%). Several conditions of stimulation were tested: IFNa 2400 U/mL, IFNg 5 ng/mL, Poly(IC) 10 µg/mL or 30 µg/mL. After 5 days, the viability, the activation (CD38) and the differentiation (CD27) of B lymphocytes were assessed by flow cytometry. Mann-Whitney (unpaired data) and Wilcoxon (paired data) were used for statistical analysis. Results: A significant increase of B lymphocytes survival was observed when cocultured with SGECs compared to B lymphocytes cultured alone, in all conditions of stimulation (p<0.05). The survival of B lymphocytes (percentage of alive cocultured B lymphocytes–percentage of alive cultured alone B lymphocytes) was increased when the cocultures were performed with SGECs from pSS patients (n=5) compared to SGECs from controls (n=5), in all conditions of stimulation (p<0.05), except IFNg. Moreover, there was a trend for an increase of B lymphocytes activation, assessed by higher percentages of CD38+ B lymphocytes when the cocultures were performed with SGECs from pSS patients compared to SGECs from controls. This difference was statistically significant (p<0.05) in the condition stimulated with TLR3 agonist (Poly(IC) 10 µ/mL). The percentage of CD27+ B lymphocytes was not affected by the cocultures and no difference between pSS and controls SGECs was observed. Conclusions: This coculture model showed a differential effect of SGECs from pSS compared to controls on B lymphocytes survival. Interestingly, there was also a trend for a higher activation level of B lymphocytes when cocultured with SGECs from pSS compared to controls. These results suggest that SGECs could play a major role in pSS pathophysiology through B lymphocytes support and activation. Disclosure of Interest: None declared.